2009
DOI: 10.1007/s11418-009-0363-3
|View full text |Cite
|
Sign up to set email alerts
|

Polyacetylene diols with antiproliferative and driving Th1 polarization effects from the marine sponge Callyspongia sp.

Abstract: A screening of 30 crude extracts of marine sponges against human promyelocytic leukemia cells (HL-60) yielded an EtOAc extract of the sponge Callyspongia sp. (Callyspongiidae) with significant activity. Further bioassay-guided fractionation of the EtOAc extract led to the isolation of three polyacetylene metabolites: a new polyacetylene diol, callyspongidiol (1), along with two known compounds, siphonodiol (2) and 14,15-dihydrosiphonodiol (3). Their structures were determined by a combination of spectroscopic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 15 publications
0
17
0
Order By: Relevance
“…Further bioassay-guided fractionation of the EtOAc extract led to the isolation of three polyacetylene metabolites: callyspongidiol (28A) [42], siphonodiol (28B), and 14,15-dihydrosiphonodiol (28C) [43]. showed significant activity against human promyelocytic leukemia cells (HL-60).…”
Section: Callyspongiamentioning
confidence: 99%
See 1 more Smart Citation
“…Further bioassay-guided fractionation of the EtOAc extract led to the isolation of three polyacetylene metabolites: callyspongidiol (28A) [42], siphonodiol (28B), and 14,15-dihydrosiphonodiol (28C) [43]. showed significant activity against human promyelocytic leukemia cells (HL-60).…”
Section: Callyspongiamentioning
confidence: 99%
“…The 1,5-dien-3-yne ether lipid raspailynes (42) have been isolated from Raspailia pumila and Raspailia ramosa (order Axinellida) [54]. The enol double bond is conjugated to both acetylenic and olefinic bonds.…”
Section: Other Spongesmentioning
confidence: 99%
“…LPS from Escherichia coli were purchased from Sigma-Aldrich Callyspongidiol and 14,15-dihydrosiphonodiol ( Fig. 1) were prepared as previously described [17]. The purity of callyspongidiol and 14,15-dihydrosiphonodiol was N99%.…”
Section: Culture Medium Reagents and Monoclonal Antibodiesmentioning
confidence: 99%
“…Siphonodiol and two related metabolites from siphonochalina truncata have been shown to inhibit H+, K+-ATPase [19]. Furthermore, callyspongidiol and 14,15-dihydrosiphonodiol exhibited antiproliferative activity against HL-60 [17]. We have recently reported that siphonodiol differentiated human monocytes DC and siphonodiol-primed DC induced the differentiation of naïve T cells towards Th1 response [20].…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation